Bleeding complications in bcr‐abl‐negative myeloproliferative neoplasms (MPN): A retrospective single‐center study of 829 MPN patients. (10th November 2021) - Wille, Kai; Huenerbein, Karlo; Jagenberg, Ellen; Sadjadian, Parvis; Becker, Tatjana; Kolatzki, Vera; Meixner, Raphael; Marchi, Hannah; Fuchs, Christiane; Griesshammer, Martin
Abstract: In patients with bcr ‐ abl ‐negative myeloproliferative neoplasms (MPN), concerns are often raised about the use of anticoagulants because of an increased bleeding risk. However, there are few MPN studies focusing on bleeding. To investigate bleeding complications in MPN, we report our retrospective, single‐center study of 829 patients with a median follow‐up of 5.5 years (range: 0.1–35.6). A first bleeding event occurred in 143 of 829 patients (17.2%), corresponding to an incidence rate of 2.29% per patient/year. During the follow‐up period, one out of 829 patients (0.1%) died due to bleeding. Regarding anticoagulation, most bleeding occurred in patients on antiplatelet therapies (60.1%), followed by patients on anticoagulation therapies (20.3%) and patients not on anticoagulation (19.6%). In multivariate analysis, administration of antiplatelet (HR 2.31 [1.43, 3.71]) and anticoagulation therapies (HR 4.06 [2.32, 7.09]), but not age, gender or mutation status, was associated with an increased bleeding risk. Comparing the "probability of bleeding‐free survival" between the MPN subtypes, no significant difference was observed ( p = 0.91, log‐rank test). Our retrospective study shows that antiplatelet and anticoagulation therapies significantly increase the risk of bleeding in MPN patients without affecting mortality. However, there is no reason to refrain from guideline‐conform primary or secondary anticoagulation in MPN patients.